Evaluation of Periodontal Status among Patients with Helicobacter Pylori and Determination of Salivary PH, Flow Rate, and Alkaline Phosphatase Level - Alewi, Marwa Dhari; Mohammed, Ahlam Taha (AL-Kindy College Medical Journal, 2024)
Background: Up to 50% of people worldwide are infected with Helicobacter pylori, a bacterium with a spiral shape and a negative Gram stain. Negative impacts on oral health, including bad breath, dental caries, recurrent aphthous stomatitis, and glossitis, are caused by this particular pathogen.Objective: This study aimed to evaluate the correlation between saliva pH, flow rate, alkaline phosphatase and periodontal status in patients with Helicobacter pylori.Subjects and Methods: From December 2021 to July 2022, a case-control study was undertaken consisting of a group of 80 participants, consisting of both H. pylori-positive individuals as the study group (40) and healthy, H. pylori-uninfected individuals as the control group (40), all between the ages of 30 and 40. Both groups provided unstimulated saliva for the study. Alkaline phosphatase levels, pH, and flow rate are all measured during saliva analysis. Upon completing this routine, an assessment of periodontal pocket depth, bleeding on probing, and plaque is conducted.Results: During the study, it was observed that the control group had lower plaque index, percentage of probing bleeding, and periodontal pocket depth compared to the study group. The difference between the two groups was statistically significant (p